Preparation method of martensitic stainless steel blade with diamond / high-entropy alloy transition layer

By preparing high-entropy alloy transition layer and diamond coating on the surface of martensite stainless steel inserts, the problem of easy falling off of diamond coating is solved, the strength and wear resistance of the insert are improved, the service life is extended, and the high-quality cutting is met. need.

CN119243154AActive Publication Date: 2025-01-03TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411310174.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-03
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively grow continuous diamond coatings with high binding force on the surface of martensite stainless steel blades, resulting in the coating being easily shedded and unable to meet the needs of high-quality cutting.

Method used

Process the micro-block array on the surface of the martensite stainless steel blade substrate and prepare a high-entropy alloy transition layer. The conical blind holes are filled by magnetron sputtering or double-layer glow ion metal seepage technology, and diamond is formed by combining microwave plasma chemical vapor deposition technology/ High entropy alloy coating.

Benefits of technology

It improves the bonding force between the diamond coating and the substrate, enhances the strength, wear resistance and corrosion resistance of the blade, extends the service life, and meets the needs of high-quality cutting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243154A_ABST
    Figure CN119243154A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a martensitic stainless steel blade with a diamond / high-entropy alloy transition layer, belongs to the technical field of metal surface coating treatment, solves the technical problem that a diamond coating cannot directly grow on the surface of the martensitic stainless steel blade, and sequentially comprises the following steps that a blade base body is made of martensitic stainless steel; micron-sized micro circular truncated cones are machined on the surface of the blade base body to form an array, and conical blind holes are formed in the top faces (upper bottom faces) of the micro circular truncated cones; then, a high-entropy alloy transition layer is prepared on the surface of the blade base body through a magnetron sputtering or double-layer glow ion cementation metallization technology, and the conical blind holes are completely filled with the high-entropy alloy transition layer and the circular truncated cone array is covered with the high-entropy alloy transition layer; and finally, after the surface of the blade blank is subjected to mechanical breeding, a microwave plasma chemical vapor deposition technology is adopted for carbonization treatment and diamond growth, and a diamond / high-entropy alloy coating which is high in hardness and good in abrasion resistance and corrosion resistance is formed on the surface of the blade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface coating treatment, and particularly relates to a method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade. Background Art

[0002] Cutting tools play a very important role in the development of the manufacturing industry. At present, domestic researchers have used martensitic stainless steel to make blades, but the wear resistance and strength of this type of steel cannot meet the needs of high-quality blade cutting, and the blade has a short service life, which restricts the development of martensitic stainless steel blades.

[0003] Diamond has extremely high hardness, and diamond tools are widely used in cutting difficult-to-process metal materials. Diamond coating-modified grinding tools have excellent mechanical properties, higher working efficiency, and longer service life, and have good application prospects. However, the base material of the blade is steel. In the preparation process of diamond-coated tools, although iron, cobalt, and nickel elements can promote graphite formation, they are not conducive to the growth of diamond coatings, and diamond coatings are easy to fall off. Therefore, directly preparing diamond coatings on the surface of steel substrates to extend their service life is not an effective solution.

[0004] High entropy alloy is an alloy composed of five or more metal elements in an equiatomic ratio or a nearly equiatomic ratio. Its unique high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect give it many excellent properties. Chinese patent document: "A carbide / diamond coating on the surface of a high entropy alloy and its preparation method" (application number: 202110517748.9) discloses that the surface of a high entropy alloy can effectively generate a diamond coating, but the coating has poor bonding with the substrate and the coating is very easy to fall off. Chinese patent document: "A Mo-based high entropy alloy and its application" (application number: 202211513271.8) discloses a method for growing a diamond coating on a Mo-based high entropy alloy. The carbonization treatment time is 30 minutes. The diamond coating prepared by this method has certain corrosion resistance and wear resistance, but the diamond coating will still fall off under the action of external force, which cannot meet the application requirements of the blade.

[0005] In summary, it is still difficult to prepare a continuous diamond coating with high bonding strength on the surface of a martensitic stainless steel blade substrate. Summary of the invention

[0006] The main purpose of the present invention is to overcome the deficiencies in the prior art and solve the technical problem that diamond coating cannot be directly grown on the surface of martensitic stainless steel blades. The present invention provides a method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade.

[0007] The design concept of the present invention is as follows: the material of the blade substrate is martensitic stainless steel. First, an array formed by micron-sized micro-cones is processed on the surface of the blade substrate, and conical blind holes are prepared on the top surface (upper bottom surface) of each micro-cone; then, a high-entropy alloy transition layer is prepared on the surface of the blade substrate by magnetron sputtering or double-layer glow ion metallization process, so that the high-entropy alloy transition layer completely fills the conical blind holes and covers the truncated cone array; finally, the surface of the blade blank is mechanically cultivated and then carbonized and diamond grown by microwave plasma chemical vapor deposition technology, so as to form a diamond / high-entropy alloy coating with high hardness, good wear resistance and corrosion resistance on the surface of the blade.

[0008] The present invention is implemented by the following technical scheme: A method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade comprises the following steps: S1. Pretreatment of blade substrate: The martensitic stainless steel blade substrate is placed in an argon protective atmosphere for annealing at 600°C for 2 hours, then cooled to room temperature with the furnace and taken out for use; the pretreatment process can reduce the residual stress inside the blade substrate, thereby providing excellent substrate material for subsequent processes, avoiding the shedding of coating materials, and extending the service life of the blade; S2, laser processing of blade substrate: take the blade substrate pretreated in step S1, grind and clean it, and then mount it on the laser processing equipment, and process the frustum array on the two side surfaces of the blade substrate respectively; the frustum array comprises a number of closely arranged micro frustums, and the shape and size of the micro frustum are as follows: the diameter of the upper bottom surface of the micro frustum is 10μm-500μm, the diameter of the lower bottom surface of the micro frustum is 1.2~3 times the diameter of the upper bottom surface of the micro frustum, the height of the micro frustum is 10μm-300μm, and the spacing between the micro frustums is equal to the diameter of the lower bottom surface of the micro frustum; a conical blind hole is set at the center of the bottom surface of the micro frustum, the diameter of the conical blind hole is 5μm-100μm, and the depth of the conical blind hole is 5μm-200μm; S3, preparing a high entropy alloy transition layer on the surface of the blade substrate, comprising the following steps: S3-1, pickling the blade substrate after laser processing in step S2 with a 0.1 mol / L HCl solution to remove oxides on the surface of the blade substrate after laser processing, and ultrasonically cleaning the blade substrate with an alcohol solution after pickling, and the ultrasonic cleaning time is 10 minutes; S3-2. According to the height of the truncated cone array, a high entropy alloy transition layer is prepared on the surface of the blade substrate in the following manner: 1) When the height of the truncated cone array is 10 μm ≤ 50 μm, a high entropy alloy transition layer is prepared on the surface of the blade substrate by a magnetron sputtering process, comprising the following steps: first, the blade substrate prepared in step S3-1 is placed in a magnetron sputtering chamber as a substrate, and a high entropy alloy is placed in a magnetron sputtering chamber as a target material, and a vacuum pump is started to evacuate the magnetron sputtering chamber until the pressure in the magnetron sputtering chamber is 1.5×10 -3 Pa; then, argon gas is introduced into the magnetron sputtering chamber as a protective gas, and the flow rate of argon gas is 70 sccm. When the pressure in the magnetron sputtering chamber is 0.5Pa, the magnetron sputtering power supply is turned on to perform magnetron sputtering on a single side of the blade substrate. The power of the magnetron sputtering power supply is 150 W, and the magnetron sputtering time is 180min-360min. A bias voltage is added during the magnetron sputtering process, and the bias voltage is -150V. Adding a bias voltage during the magnetron sputtering process can effectively improve the bonding force between the blade and the film, and the high entropy alloy transition layer is prepared by magnetron sputtering on a single side of the blade substrate. The high entropy alloy transition layer is filled in the conical blind hole of the micro-truncated cone and completely covers the truncated cone array; finally, after the magnetron sputtering treatment is completed, the magnetron sputtering power supply is turned off, and the blade blank is taken out for standby; 2) When the height of the truncated cone array is 50 μm ≤ ≤ 300 μm, a high entropy alloy transition layer is prepared on the surface of the blade substrate by a double-layer glow ion metallization process, including the following steps: First, the blade substrate prepared in step S3-1 is placed in a double-layer glow infiltration furnace, and argon gas is introduced into the double-layer glow infiltration furnace as a protective gas, and the flow rate of argon gas is 70 sccm; then, the double-layer glow infiltration furnace is started, and a high entropy alloy is infiltrated into the surface of the blade substrate. The infiltration time is 180min-360min, and the double-layer glow ion infiltration of the blade substrate surface is completed to prepare a high entropy alloy transition layer, and the high entropy alloy transition layer is filled in the conical blind holes of the micro-truncated cone and completely covers the truncated cone array; finally, the blade blank is taken out from the double-layer glow infiltration furnace, and the surface of the blade blank is finely polished and then set aside; S4, mechanical breeding: Diamond powder with a particle size of 50nm-100nm is evenly applied on the surface of the blade blank, and then the blade is immersed in a diamond suspension and ultrasonically treated for 10 min; S5. Carbonization treatment: First, place the blade blank after mechanical breeding in step S4 in a microwave plasma chemical vapor deposition carbonization chamber, turn on the mechanical pump, evacuate the air pressure in the carbonization chamber to a vacuum state, and then introduce hydrogen with a hydrogen flow rate of 400 sccm. When the air pressure in the carbonization chamber reaches 0.4 KPa, turn on the microwave power supply with a power of 0.6 kW. Then, when the power of the microwave power supply is increased to 1kW-2.5kW and the air pressure in the carbonization chamber reaches 2kPa-5kPa, introduce methane gas with a volume concentration of 1%-3% for carbonization treatment, with a methane flow rate of 40sccm-120sccm, a carbonization treatment temperature of 600℃-700℃, and a carbonization treatment time of 60min-180min to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer.

[0009] Furthermore, in step S3-2, the high entropy alloy is Mo 0.5 (TiZrTaW) 0.5 Or ZrNbTaMo.

[0010] The beneficial effects of the present invention are: 1) The present invention prepares a truncated cone array on the blade surface, so that the high entropy alloy transition layer and the blade substrate are more firmly bonded, and the high entropy alloy transition layer improves the bonding ability between the martensitic stainless steel substrate and the diamond coating; 2) During the carbonization process, lowering the carbonization temperature of microwave plasma chemical vapor deposition to 600℃-700℃ will not change the microstructure of martensitic steel.

[0011] In summary, the continuous diamond coating grown on the blade surface of the present invention has stronger bonding force and adhesion, and the strength, wear resistance and corrosion resistance of the prepared blade are improved. It has higher work efficiency and longer service life, and has broad application prospects in the field of blade surface hardening. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A process flow chart of a diamond / high entropy alloy coated blade prepared by the present invention; Figure 2 The SEM surface morphology of the martensitic stainless steel blade with a diamond / high entropy alloy transition layer prepared in Example 1; wherein the methane concentration is 3% and the carbonization treatment time is 120 min; Figure 3 This is the SEM surface morphology of the blade without high entropy alloy transition layer after carbonization; the methane concentration is 3% and the carbonization treatment time is 120 minutes; Figure 4This is the SEM surface morphology of the martensitic stainless steel blade with a diamond / high entropy alloy transition layer prepared in Example 2; wherein the methane concentration is 3% and the carbonization treatment time is 180 min. DETAILED DESCRIPTION

[0013] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example 1

[0014] In this embodiment 1, the material of the blade substrate is martensitic stainless steel; the high entropy alloy transition layer is Mo-based high entropy alloy with a nominal composition of Mo. 0.5 (TiZrTaW) 0.5 , and the atomic ratios of Ti element, Zr element, Ta element and W element are equal.

[0015] like Figure 1 The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade shown in the figure comprises the following steps: S1. Pretreatment of the blade substrate: The martensitic stainless steel blade substrate is placed in an argon protective atmosphere for annealing at a temperature of 600°C for 2 hours, then cooled to room temperature with the furnace and taken out for use; S2, laser processing of blade substrate: take the blade substrate pretreated in step S1, grind and clean it, and then mount it on the laser processing equipment, and process a frustum array on the surfaces of both sides of the blade substrate respectively; the frustum array includes a number of closely arranged micro frustums, and the shape and size of the micro frustums are as follows: the diameter of the upper bottom surface of the micro frustum is 10μm, the diameter of the lower bottom surface of the micro frustum is 15μm, the height of the micro frustum is 10μm, and the spacing between the micro frustums is 15μm; a conical blind hole is set at the center of the bottom surface of the micro frustum, the diameter of the conical blind hole is 5μm, and the depth of the conical blind hole is 5μm; S3, preparing a high entropy alloy transition layer on the surface of the blade substrate, comprising the following steps: S3-1, pickling the blade substrate after laser processing in step S2 with a 0.1 mol / L HCl solution to remove oxides on the surface of the blade substrate after laser processing, and ultrasonically cleaning the blade substrate with an alcohol solution after pickling, and the ultrasonic cleaning time is 10 minutes; S3-2. According to the height of the truncated cone array, a high entropy alloy transition layer is prepared on the surface of the blade substrate in the following manner: Since the height of the truncated cone array in this embodiment 1 is 10 μm, a magnetron sputtering process is used to prepare a high entropy alloy transition layer on the surface of the blade substrate, including the following steps: first, the blade substrate prepared in step S3-1 is placed in a magnetron sputtering chamber as a substrate, and Mo 0.5 (TiZrTaW) 0.5The high entropy alloy was placed in the magnetron sputtering chamber as the target material, and the vacuum pump was started to evacuate the chamber to a pressure of 1.5×10 -3 Pa; then, argon gas is introduced into the magnetron sputtering chamber as a protective gas, and the flow rate of argon gas is 70 sccm. When the pressure in the magnetron sputtering chamber is 0.5Pa, the magnetron sputtering power supply is turned on to perform magnetron sputtering on a single side of the blade substrate. The power of the magnetron sputtering power supply is 150 W, and the magnetron sputtering time is 180min. During the magnetron sputtering process, a bias voltage is added, and the bias voltage is -150V. The high entropy alloy transition layer is prepared by magnetron sputtering on a single side of the blade substrate. The high entropy alloy transition layer is filled in the conical blind holes of the micro-truncated cone and completely covers the truncated cone array; finally, the blade substrate is taken out and turned over, and the above magnetron sputtering steps are repeated to prepare a high entropy alloy transition layer on the other side of the blade substrate. After the magnetron sputtering treatment is completed, the magnetron sputtering power supply is turned off, and the blade blank is taken out for standby; S4, mechanical breeding: Diamond powder with a particle size of 50 nm was evenly applied on the surface of the blade blank, and then the blade was immersed in a diamond suspension and ultrasonically treated for 10 min; S5, carbonization treatment: First, place the blade blank after mechanical breeding in step S4 in a microwave plasma chemical vapor deposition carbonization chamber, turn on the mechanical pump, pump the air pressure in the carbonization chamber to a vacuum state, and then introduce hydrogen, the hydrogen flow rate is 400sccm, and turn on the microwave power supply when the air pressure in the carbonization chamber is 0.4 KPa, and the power of the microwave power supply is 0.6 kW; then, when the power of the microwave power supply is increased to 1.2kW and the air pressure in the carbonization chamber reaches 2.4kPa, introduce methane gas with a volume concentration of 3% for carbonization treatment, the flow rate of methane is 120sccm, the carbonization treatment temperature is 700℃, and the carbonization treatment time is 120min. During the carbonization treatment, a high hardness, high wear resistance, and corrosion resistance diamond coating is generated on the carbide surface on the high entropy alloy transition layer. After the carbonization and heat preservation is completed, the power is gradually reduced until it is zero, and the power is turned off to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer.

[0016] The surface structure and morphology of the martensitic stainless steel blade with diamond / high entropy alloy transition layer prepared in Example 1 were observed by scanning electron microscopy. Figure 2 As shown in the figure, the continuous particle coating is plated with Mo 0.5 (TiZrTaW) 0.5 A continuous diamond coating grows on the blade surface of the high entropy alloy transition layer, and the diamond coating does not fall off.

[0017] Compared with Example 1, the SEM surface morphology of the blade without the high entropy alloy transition layer after carbonization is as follows: Figure 3As shown in the figure, the carbonization process parameters are: methane concentration is 3%, carbonization temperature is 700℃, and carbonization time is 120min. Figure 3 The low content of white particles indicates that the diamond particles are not easy to grow directly on the blade surface and are prone to fall off. Example 2

[0018] like Figure 1 The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade shown in the embodiment 2, the materials of the blade substrate and the high entropy alloy transition layer in the embodiment 2 are the same as those in the embodiment 1, and the steps S1 to S4 in the embodiment 2 are the same as those in the embodiment 1, and the only difference is the carbonization treatment in step S5: First, the blade blank after mechanical breeding in step S4 is placed in a microwave plasma chemical vapor deposition carbonization chamber, the mechanical pump is turned on, the air pressure in the carbonization chamber is evacuated to a vacuum state, and hydrogen is introduced with a hydrogen flow rate of 400 sccm. When the air pressure in the carbonization chamber is 0.4 KPa, the microwave power supply is turned on, and the power of the microwave power supply is 0.6 kW; then, when the power of the microwave power supply is increased to 1.2 kW and the air pressure in the carbonization chamber reaches 2.4 kPa, methane gas with a volume concentration of 3% is introduced for carbonization treatment, the methane flow rate is 120 sccm, the carbonization treatment temperature is 700°C, and the carbonization treatment time is 180 min, to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer.

[0019] The surface structure and morphology of the martensitic stainless steel blade with diamond / high entropy alloy transition layer prepared in Example 2 were observed by scanning electron microscopy. Figure 4 As shown in the figure, the continuous particle coating is plated with Mo 0.5 (TiZrTaW) 0.5 A continuous diamond coating is generated on the blade surface of the high entropy alloy transition layer, and the diamond coating does not fall off. Example 3

[0020] like Figure 1 The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade shown in the embodiment 3, the materials of the blade substrate and the high entropy alloy transition layer in the embodiment 3 are the same as those in the embodiment 1, and the steps S1 to S4 in the embodiment 3 are the same as those in the embodiment 1, and the only difference is the carbonization treatment in step S5: First, the blade blank after mechanical breeding in step S4 is placed in a microwave plasma chemical vapor deposition carbonization chamber, the mechanical pump is turned on, the air pressure in the carbonization chamber is evacuated to a vacuum state, and hydrogen is introduced with a hydrogen flow rate of 400 sccm. When the air pressure in the carbonization chamber is 0.4 KPa, the microwave power supply is turned on, and the power of the microwave power supply is 0.6 kW; then, when the power of the microwave power supply is increased to 1.2 kW and the air pressure in the carbonization chamber reaches 2.4 kPa, methane gas with a volume concentration of 3% is introduced for carbonization treatment, the methane flow rate is 40 sccm, the carbonization treatment temperature is 700°C, and the carbonization treatment time is 60 min, to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer. Example 4

[0021] like Figure 1 The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade shown in the embodiment 4 is that the materials of the blade substrate and the high entropy alloy transition layer are the same as those in the embodiment 1, and the steps S1 to S4 in the embodiment 4 are the same as those in the embodiment 1, and the only difference is the carbonization treatment in step S5: First, the blade blank after mechanical breeding in step S4 is placed in a microwave plasma chemical vapor deposition carbonization chamber, the mechanical pump is turned on, the air pressure in the carbonization chamber is evacuated to a vacuum state, and hydrogen is introduced, the hydrogen flow rate is 400 sccm, and the microwave power supply is turned on when the air pressure in the carbonization chamber is 0.4 KPa, and the power of the microwave power supply is 0.6 kW; then, when the power of the microwave power supply is increased to 1.2 kW and the air pressure in the carbonization chamber reaches 2.4 kPa, methane gas with a volume concentration of 3% is introduced for carbonization treatment, the methane flow rate is 60 sccm, the carbonization treatment temperature is 650°C, and the carbonization treatment time is 120 min. Compared with Examples 1 to 3, the temperature is lowered and the growth time is extended during the carbonization treatment in Example 4, and a high hardness, high wear resistance, and corrosion resistance diamond film can also be generated on the carbide surface on the high entropy alloy transition layer to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer. Example 5

[0022] like Figure 1 The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade shown in the figure, the material of the blade substrate in this embodiment 5 is martensitic stainless steel, the difference is that the nominal composition of the high entropy alloy transition layer is TiZrNbTaMo, and the atomic ratios between the Ti element, the Zr element, the Nb element, the Ta element and the Mo element are equal; in this embodiment 5, steps S1 to S4 are the same as those in embodiment 1 except that the material of the high entropy alloy transition layer is different, and the difference is that step S5 is carbonized: First, the blade blank after mechanical breeding in step S4 is placed in a microwave plasma chemical vapor deposition carbonization chamber, the mechanical pump is turned on, the air pressure in the carbonization chamber is evacuated to a vacuum state, and hydrogen is introduced with a hydrogen flow rate of 400 sccm. When the air pressure in the carbonization chamber is 0.4 KPa, the microwave power supply is turned on, and the power of the microwave power supply is 0.6 kW; then, when the power of the microwave power supply is increased to 1.2 kW and the air pressure in the carbonization chamber reaches 2.4 kPa, methane gas with a volume concentration of 3% is introduced for carbonization treatment, the methane flow rate is 80 sccm, the carbonization treatment temperature is 700°C, and the carbonization treatment time is 60 min, to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer. Example 6

[0023] In this embodiment 6, the material of the blade substrate is martensitic stainless steel; the nominal composition of the high entropy alloy transition layer is TiZrNbTaMo, and the atomic ratios among Ti element, Zr element, Nb element, Ta element and Mo element are equal.

[0024] like Figure 1 The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade shown in the figure comprises the following steps: S1. Pretreatment of the blade substrate: The martensitic stainless steel blade substrate is placed in an argon protective atmosphere for annealing at a temperature of 600°C for 2 hours, then cooled to room temperature with the furnace and taken out for use; S2, laser processing of blade substrate: take the blade substrate pretreated in step S1, grind and clean it, and then mount it on the laser processing equipment, and process the frustum array on the two side surfaces of the blade substrate respectively; the frustum array includes a number of closely arranged micro frustums, and the shape and size of the micro frustums are as follows: the diameter of the upper bottom surface of the micro frustum is 50μm, the diameter of the lower bottom surface of the micro frustum is 75μm, the height of the micro frustum is 50μm, and the spacing between the micro frustums is 75μm; a conical blind hole is set at the center of the bottom surface of the micro frustum, the diameter of the conical blind hole is 25μm, and the depth of the conical blind hole is 25μm; S3, preparing a high entropy alloy transition layer on the surface of the blade substrate, comprising the following steps: S3-1, pickling the blade substrate after laser processing in step S2 with a 0.1 mol / L HCl solution to remove oxides on the surface of the blade substrate after laser processing, and ultrasonically cleaning the blade substrate with an alcohol solution after pickling, and the ultrasonic cleaning time is 10 minutes; S3-2. According to the height of the truncated cone array, a high entropy alloy transition layer is prepared on the surface of the blade substrate in the following manner: Since the height of the truncated cone array in this embodiment 6 is 50 μm, a double-layer glow ion metallization process is used to prepare a high entropy alloy transition layer on the surface of the blade substrate, including the following steps: First, the blade substrate prepared in step S3-1 is placed in a double-layer glow infiltration furnace, and argon gas is introduced into the double-layer glow infiltration furnace as a protective gas, and the flow rate of argon gas is 70 sccm; then, the double-layer glow infiltration furnace is started, and a high entropy alloy is infiltrated into the surface of the blade substrate. The infiltration time is 180 minutes, and the double-layer glow ion infiltration of the blade substrate surface is completed to prepare a high entropy alloy transition layer, and the high entropy alloy transition layer is filled in the conical blind holes of the micro-truncated cone and completely covers the truncated cone array; finally, the blade blank is taken out from the double-layer glow infiltration furnace, and the surface of the blade blank is finely polished and then set aside; S4, mechanical breeding: Diamond powder with a particle size of 50 nm was evenly applied on the surface of the blade blank, and then the blade was immersed in a diamond suspension and ultrasonically treated for 10 min; S5, carbonization treatment: First, place the blade blank after mechanical breeding in step S4 in a microwave plasma chemical vapor deposition carbonization chamber, turn on the mechanical pump, pump the air pressure in the carbonization chamber to a vacuum state, and then introduce hydrogen, the hydrogen flow rate is 400sccm, and turn on the microwave power supply when the air pressure in the carbonization chamber is 0.4 KPa, and the power of the microwave power supply is 0.6 kW; then, when the power of the microwave power supply is increased to 1.2kW and the air pressure in the carbonization chamber reaches 2.4kPa, introduce methane gas with a volume concentration of 3% for carbonization treatment, the flow rate of methane is 120sccm, the carbonization treatment temperature is 700℃, and the carbonization treatment time is 120min. During the carbonization treatment, a high hardness, high wear resistance, and corrosion resistance diamond coating is generated on the carbide surface on the high entropy alloy transition layer. After the carbonization and heat preservation is completed, the power is gradually reduced until it is zero, and the power is turned off to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer.

[0025] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade, characterized in that: The following steps are involved: S1. Pretreatment of the blade substrate: The martensitic stainless steel blade substrate is placed in an argon protective atmosphere for annealing at a temperature of 600°C for 2 hours, then cooled to room temperature with the furnace and taken out for use; S2, laser processing of blade substrate: take the blade substrate pretreated in step S1, grind and clean it, and then mount it on the laser processing equipment, and process the frustum array on the two side surfaces of the blade substrate respectively; the frustum array comprises a number of closely arranged micro frustums, and the shape and size of the micro frustum are as follows: the diameter of the upper bottom surface of the micro frustum is 10μm-500μm, the diameter of the lower bottom surface of the micro frustum is 1.2~3 times the diameter of the upper bottom surface of the micro frustum, the height of the micro frustum is 10μm-300μm, and the spacing between the micro frustums is equal to the diameter of the lower bottom surface of the micro frustum; a conical blind hole is set at the center of the bottom surface of the micro frustum, the diameter of the conical blind hole is 5μm-100μm, and the depth of the conical blind hole is 5μm-200μm; S3, preparing a high entropy alloy transition layer on the surface of the blade substrate, comprising the following steps: S3-1, pickling the blade substrate after laser processing in step S2 with a 0.1 mol / L HCl solution to remove oxides on the surface of the blade substrate after laser processing, and ultrasonically cleaning the blade substrate with an alcohol solution after pickling, and the ultrasonic cleaning time is 10 minutes; S3-2. According to the height of the truncated cone array, a high entropy alloy transition layer is prepared on the surface of the blade substrate in the following manner: 1) When the height of the truncated cone array is 10 μm ≤ 50 μm, a high entropy alloy transition layer is prepared on the surface of the blade substrate by a magnetron sputtering process, comprising the following steps: first, the blade substrate prepared in step S3-1 is placed in a magnetron sputtering chamber as a substrate, and a high entropy alloy is placed in a magnetron sputtering chamber as a target material, and a vacuum pump is started to evacuate the magnetron sputtering chamber until the pressure in the magnetron sputtering chamber is 1.5×10 -3 Pa; then, argon gas is introduced into the magnetron sputtering chamber as a protective gas, and the flow rate of argon gas is 70 sccm. When the pressure in the magnetron sputtering chamber is 0.5Pa, the magnetron sputtering power supply is turned on to perform magnetron sputtering on a single side of the blade substrate. The power of the magnetron sputtering power supply is 150 W, and the magnetron sputtering time is 180min-360min. During the magnetron sputtering process, a bias voltage is added, and the bias voltage is -150V. The high entropy alloy transition layer is prepared by magnetron sputtering on a single side of the blade substrate. The high entropy alloy transition layer is filled in the conical blind holes of the micro-truncated cone and completely covers the truncated cone array; finally, after the magnetron sputtering treatment is completed, the magnetron sputtering power supply is turned off, and the blade blank is taken out for use; 2) When the height of the truncated cone array is 50 μm ≤ ≤ 300 μm, a high entropy alloy transition layer is prepared on the surface of the blade substrate by a double-layer glow ion metallization process, including the following steps: First, the blade substrate prepared in step S3-1 is placed in a double-layer glow infiltration furnace, and argon gas is introduced into the double-layer glow infiltration furnace as a protective gas, and the flow rate of argon gas is 70 sccm; then, the double-layer glow infiltration furnace is started, and a high entropy alloy is infiltrated into the surface of the blade substrate. The infiltration time is 180min-360min, and the double-layer glow ion infiltration of the blade substrate surface is completed to prepare a high entropy alloy transition layer, and the high entropy alloy transition layer is filled in the conical blind holes of the micro-truncated cone and completely covers the truncated cone array; finally, the blade blank is taken out from the double-layer glow infiltration furnace, and the surface of the blade blank is finely polished and then set aside; S4, mechanical breeding: Diamond powder with a particle size of 50nm-100nm is evenly applied on the surface of the blade blank, and then the blade is immersed in a diamond suspension and ultrasonically treated for 10 min; S5. Carbonization treatment: First, place the blade blank after mechanical breeding in step S4 in a microwave plasma chemical vapor deposition carbonization chamber, turn on the mechanical pump, evacuate the air pressure in the carbonization chamber to a vacuum state, and then introduce hydrogen with a hydrogen flow rate of 400 sccm. When the air pressure in the carbonization chamber reaches 0.4 KPa, turn on the microwave power supply with a power of 0.6 kW. Then, when the power of the microwave power supply is increased to 1kW-2.5kW and the air pressure in the carbonization chamber reaches 2kPa-5kPa, introduce methane gas with a volume concentration of 1%-3% for carbonization treatment, with a methane flow rate of 40 sccm-120 sccm, a carbonization treatment temperature of 600°C-700°C, and a carbonization treatment time of 60min-180min to obtain a martensitic stainless steel blade with a diamond / high entropy alloy transition layer.

2. The method for preparing a diamond / high entropy alloy transition layer martensitic stainless steel blade according to claim 1, characterized in that: In step S3-2, the high entropy alloy is Mo 0.5 (TiZrTaW) 0.5 Or ZrNbTaMo.

Citation Information

Patent Citations

  • Reflection element with inner surface provided with micro-convex structure array and manufacturing method of reflection element

    CN104742297A

  • Preparation method of nano-diamond coating and nano-diamond blade

    CN105506574A

  • Method for improving optical transmittance of diamond substrate

    CN115491637A

  • Method for preparing high-entropy alloy composites reinforced by diamond particles

    US20230257856A1

  • Method for improving film-substrate bonding strength of diamond-like carbon coating on medical metal surface

    WO2023245858A1